Interface enriched highly interlaced layered MoS2/NiS2 nanocomposites for the photocatalytic degradation of rhodamine B dye. Issue 31 (27th May 2021) - Harish, S.; Bharathi, P.; Prasad, Prachi; Ramesh, R.; Ponnusamy, S.; Shimomura, M.; Archana, J.; Navaneethan, M.
Abstract : The photocatalytic performance of MoS2 /NiS2 nanocomposites was studied by the degradation of rhodamine B (RhB). Ni-4 sample shows higher photocatalytic activity with a maximum degradation of 90.61% under visible light irradiation for 32 min. Abstract : In the past few decades, air and water pollution by organic dyes has become a serious concern due to their high toxicity. Removal of these organic dyes from polluted water bodies is a serious environmental concern and the development of new advanced photocatalytic materials for decomposing organic dyes can be a good solution. In this work, layered molybdenum disulfide/nickel disulfide (MoS2 /NiS2 ) nanocomposites with various NiS2 content was synthesized by a one-step hydrothermal method using citric acid as a reducing agent. The X-ray diffraction pattern shows the hexagonal and cubical crystal structure of MoS2 and NiS2, respectively. Morphological analysis confirms the formation of MoS2 /NiS2 nanosheets. The elemental composition of the samples was carried out by XPS, which shows a significant interaction between NiS2 and MoS2 . The photocatalytic performance of MoS2 /NiS2 nanocomposites was studied by the degradation of rhodamine B (RhB). Ni-4 sample shows higher photocatalytic activity with a maximum degradation of 90.61% under visible light irradiation for 32 min.